Factors associated with gingival inflammation among adults with systemic sclerosis. Issue 1 (24th April 2013) - Yuen, HK; Weng, Y; Reed, SG; Summerlin, LM; Silver, RM
Abstract Objective To identify factors associated with increased gingival inflammation in adults with systemic sclerosis (SSc, scleroderma). Methods In this cross‐sectional study, forty‐eight adults with SSc received assessment of gingival inflammation using Löe and Silness gingival index (LSGI), measurement of oral aperture and evaluation of manual dexterity to perform oral hygiene using the Toothbrushing Ability Test, as well as completion of an oral health‐related questionnaire. Results Three explanatory variables in the final multiple predictor models for the LSGI outcome were statistically significant – manual dexterity to perform oral hygiene, flossing in the evening and SSc subtype, with higher (i.e., worse) LSGI score among those with impaired manual dexterity, not flossing in the evening and diffuse form of SSc. In addition, posterior teeth had higher LSGI scores compared with that of the anterior teeth after adjusting for other variables. Conclusions Results suggest that dental health professionals take manual dexterity into consideration when educating patients with SSc to improve their oral hygiene and educate them on paying more attention on cleaning their posterior teeth and the importance of flossing in the evening – especially those who only floss once a day or less often.